Optimalisasi Komunikasi dan Visualisasi sebagai Upaya Mendukung Program Transformasi Polri yang PRESISI melalui Kegiatan Sosialisasi - Yulianti, Elis; Kristanto, Harys; Reza, Yolandita Angga; Kurniawan, Wahyu; Subiakto, Vania Utamie; Yuda, Mulfi Sandi (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aims to support the Indonesian National Police (Polri) transformation program toward a PRESISI institution (Predictive, Responsibility, and Fair Transparency) through the strengthening of communication strategies and visualization. The program involved 50 members of the Bekasi Police as training participants, focusing on enhancing public communication capacity and the utilization of visual media as an effective tool for delivering messages to the community. The methods applied included participatory training, interactive lectures, and simulations in designing visual messages aligned with the PRESISI principles. The results indicated an improvement in participants’ understanding and skills in managing institutional communication that is educational, informative, and persuasive. Moreover, participants were able to design simple yet communicative visual content to support the dissemination of Polri’s policies and programs to the public. This activity is expected to serve as an initial step in establishing more humanistic and transparent communication patterns between the police and the community, enabling the Bekasi Police to become a model for implementing the PRESISI transformation program.This community service activity aims to support the Indonesian National Police (Polri) transformation program toward a PRESISI institution (Predictive, Responsibility, and Fair Transparency) through the strengthening of communication strategies and visualization. The program involved 50 members of the Bekasi Police as training participants, focusing on enhancing public communication capacity and the utilization of visual media as an effective tool for delivering messages to the community. The methods applied included participatory training, interactive lectures, and simulations in designing visual messages aligned with the PRESISI principles. The results indicated an improvement in participants’ understanding and skills in managing institutional communication that is educational, informative, and persuasive. Moreover, participants were able to design simple yet communicative visual content to support the dissemination of Polri’s policies and programs to the public. This activity is expected to serve as an initial step in establishing more humanistic and transparent communication patterns between the police and the community, enabling the Bekasi Police to become a model for implementing the PRESISI transformation program.This community service activity aims to support the Indonesian National Police (Polri) transformation program toward a PRESISI institution (Predictive, Responsibility, and Fair Transparency) through the strengthening of communication strategies and visualization. The program involved 50 members of the Bekasi Police as training participants, focusing on enhancing public communication capacity and the utilization of visual media as an effective tool for delivering messages to the community. The methods applied included participatory training, interactive lectures, and simulations in designing visual messages aligned with the PRESISI principles. The results indicated an improvement in participants’ understanding and skills in managing institutional communication that is educational, informative, and persuasive. Moreover, participants were able to design simple yet communicative visual content to support the dissemination of Polri’s policies and programs to the public. This activity is expected to serve as an initial step in establishing more humanistic and transparent communication patterns between the police and the community, enabling the Bekasi Police to become a model for implementing the PRESISI transformation program.